2017
DOI: 10.1007/s10048-017-0526-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel GFM2 variants associated with early-onset neurological presentations of mitochondrial disease and impaired expression of OXPHOS subunits

Abstract: Mitochondrial diseases are characterised by clinical, molecular and functional heterogeneity, reflecting their bi-genomic control. The nuclear gene GFM2 encodes mtEFG2, a protein with an essential role during the termination stage of mitochondrial translation. We present here two unrelated patients harbouring different and previously unreported compound heterozygous (c.569G>A, p.(Arg190Gln); c.636delA, p.(Glu213Argfs*3)) and homozygous (c.275A>C, p.(Tyr92Ser)) recessive variants in GFM2 identified by whole exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In the GWAS catalog, GFM1 appears associated with the electrocardiographic PR interval, diastolic blood pressure, and diarrhea. Mutations in GFM2 result in COXPD39 with complex IV deficiency and subsequent ataxic hypotonia followed by Leigh syndrome leukodystrophy [ 68 ]. For TUFM, mutations trigger COXPD4 with complex IV deficiency and rapidly progressive encephalopathy [ 69 ].…”
Section: Genotype–phenotype Correlationmentioning
confidence: 99%
“…In the GWAS catalog, GFM1 appears associated with the electrocardiographic PR interval, diastolic blood pressure, and diarrhea. Mutations in GFM2 result in COXPD39 with complex IV deficiency and subsequent ataxic hypotonia followed by Leigh syndrome leukodystrophy [ 68 ]. For TUFM, mutations trigger COXPD4 with complex IV deficiency and rapidly progressive encephalopathy [ 69 ].…”
Section: Genotype–phenotype Correlationmentioning
confidence: 99%
“…In the GWAS catalog, GFM1 appears associated with the electrocardiographic PR interval, diastolic blood pressure, and diarrhea. Mutations in GFM2 result in COXPD39 with complex IV deficiency and subsequent ataxic hypotonia followed by Leigh syndrome leukodystrophy [64]. For TUFM, mutations trigger COXPD4 with complex IV deficiency and rapidly progressive encephalopathy [65].…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
“…WES was used to identify compound heterozygous (c.569G>A, p.Arg190Gln; c.636delA, p.Glu213Argfs * 3) and homozygous (c.275A>C, p.Tyr92Ser) recessive variants of GFM2 in patients presenting in early childhood with global developmental delay, elevated cerebrospinal fluid levels of lactate, and abnormalities on cranial magnetic resonance imaging (Zhang et al, 2016). Further research also identified these recessive GFM2 variants in two unrelated patients with early-onset neurological presentations of mitochondrial disease (Glasgow et al, 2017).…”
Section: Mitochondrial Translation Recyclingmentioning
confidence: 99%
“…The mtEF-G1 elongation factor displays mitoribosome translocation activity. The EF-G2mt factor disassembles the mitoribosome at the end of translation to allow a subsequent protein-synthesis cycle ( Glasgow et al, 2017 ).…”
Section: Mitochondrial Translation Elongation and Diseasementioning
confidence: 99%